2019
DOI: 10.3390/pr7030125
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Method in the Optimization of a Rotary Pan-Equipped process for Increased Efficiency of Slow-Release Coated Urea

Abstract: The high solubility of urea in water and its consequent leaching into the soil adversely prevents its full assimilation by plants. An improved slow-release process could effectively minimise the loss of fertilizer material and thus mitigate the associated environmental pollution. In this study, the effects of the operational variables on the efficiency of the urea coating process in a rotary pan have been systematically analysed. A mixture of gypsum-sulphur was used as the coating material with refined water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…The controlled release of nitrogen fertilizer was key to the wheat plant growth, especially in waterlogged and salt stress. Many studies found that a higher grain yield can be attained by applying controlled-release SCU fertilization [23]. SCU increased grain yield efficiently by lowering rhizosphere pH, and the results were consistent with findings of a previous study [47].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The controlled release of nitrogen fertilizer was key to the wheat plant growth, especially in waterlogged and salt stress. Many studies found that a higher grain yield can be attained by applying controlled-release SCU fertilization [23]. SCU increased grain yield efficiently by lowering rhizosphere pH, and the results were consistent with findings of a previous study [47].…”
Section: Discussionsupporting
confidence: 90%
“…One of the good slow-release nitrogen fertilizers is sulfur-coated urea (SCU), which promotes wheat growth and development. The wheat crop has a positive correlation between "S" and "N" elements [23]. The S element is a secondary and fungicide with acidic possessions that neutralize the alkalinity of soil [24].…”
Section: Introductionmentioning
confidence: 99%
“…The coating of urea particles was performed in a stainless-steel rotary pan of 60 cm diameter and 12 cm pan height ( Scheme 1 ) at ambient conditions as previously described. 33 As shown in Table 3 , six different coating formulations, consisting of combinations of gypsum, sulfur, and zeolite at various compositions, were studied. It should be noted that although each component has been used as a coating material for SRFs, 30 , 38 in this study, gypsum plaster played another role as a binder, and it was therefore a base material in all formulations.…”
Section: Experimental Proceduresmentioning
confidence: 99%
“…The dried coated urea granules were then collected for further studies. The other coating parameters and their corresponding values based on the previous study 33 are also summarized in Table 4 .…”
Section: Experimental Proceduresmentioning
confidence: 99%
“…Eghbali Babadi et al [12] analyzed the operational variables effect on the urea coating process efficiency in a rotary pan. And Rozbroj et al [13] investigated cylindrical pellet size optimization using discrete element method model.…”
Section: Optimization Issuesmentioning
confidence: 99%